Traces of Social History in Batu Bara Songket Traditional Crafts in Batubara Regency, North Sumatra Province - Hadiani Fitri; Zuraidah Adlina (Yupa: Historical Studies Journal, 2023)
This study aims to describe the traces of social history in the traditional craft of Batubara songket in Batubara Regency. Songket Batu Bara woven fabric continues to evolve with the times, songket has even become a popular choice for traditional Malay wedding attire, especially in Batu Bara regency. This study uses a descriptive qualitative research method. Data collection was carried out by observation, document analysis, interviews, and literature studies. Qualitative descriptive data analysis techniques were used in this study. The results of this study indicate that the Batu Bara Malay songket woven fabric is a traditional woven fabric that has become a cultural heritage for the Batu Bara people. Batu Bara Malay Songket was already known during the reign of the Batu Bara Sultanate. The functions of the Malay Batu Bara woven songket include, as a reinforcement of identity, an expression of love, to maintaining the continuity and stability of Malay culture, when someone wears a Malay songket, they are already carrying out the function of the Malay songket woven fabric and also developing culture.